The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-33062010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Novidades taxonômicas em Croton sect. Argyroglossum Baill. e C. sect. Lasiogyne Klotzsch (Crotonoideae-Euphorbiaceae)

Abstract: Nove novos sinônimos, um neótipo e três lectotipificações de espécies de Croton são propostos. Além disso, C.schomburgkianus A. P. S. Gomes & M. F. Sales é designada como um novo nome para C. nervosus Klotzsch. Na seção Argyroglossum Baill., Croton argyroglossus Baill. e C. micans var. argyroglossus Baill. são sinonimizadas sob C. argyrophyllus Kunth; C. alagoensis Müll. Arg. e C. floribundus var. piauhiensis Rizzini sinonimizadas sob C. blanchetianus; C. micans var. pubescens Müll. Arg., Croton argyrophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We recently showed that the essential oil of leaves from Croton argyrophyllus Kunth displays anti‐inflammatory activity in rodents, as evidenced by the significant inhibition of oedema formation and leukocyte influx induced by carrageenan . In the same study, we also showed that the essential oil of C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the essential oil of leaves from Croton argyrophyllus Kunth displays anti‐inflammatory activity in rodents, as evidenced by the significant inhibition of oedema formation and leukocyte influx induced by carrageenan . In the same study, we also showed that the essential oil of C .…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that the essential oil obtained from species of Croton has multiple biological effects, such as antinociceptive, antiinflammatory, healing and antihypertensive. [4][5][6][7][8] We recently showed that the essential oil of leaves from Croton argyrophyllus Kunth [9,10] displays anti-inflammatory activity in rodents, as evidenced by the significant inhibition of oedema formation and leukocyte influx induced by carrageenan. [11] In the same study, we also showed that the essential oil of C. argyrophyllus leaves presents an antioxidant activity, which could be, in part, responsible for the anti-inflammatory actions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Nowadays, that plant species has been correctly identified as C. blanchetianus Baill., and a few reports mention that C. sonderianus and C. blanchetianus are indeed synonyms. 10,11 Several biological activities of Croton species have been reported, among them: the antimalarial action and low acute and subacute toxicity of the leaf extract of Croton macrostachyus, 1 the inhibition of chikungunya virus replication by Croton mauritianus leaf extract, 12 the antiulcerogenic action and the low acute and subacute toxicity of Croton urucurana extract. 13 Ethanol extracts of the trunks, leaves, and seeds of Croton tiglium showed some antifungal activities against three dermatophytes.…”
Section: Introductionmentioning
confidence: 99%